New progress and prospect of earthquake-related resistivity experiments - Tao Zhu (地球与行星物理论评, 2021)
Precise prediction is an effective way to prevent earthquake and reduce disaster. Geoelectrical resistivity is a proofed and effective earthquake precursor and has played and been playing important role in earthquake monitoring and prediction in our homeland since 1966. Lab/field experiments on characteristics, trend and mechanism of resistivity changes have not been ceased since 1960s associated with the applications of geoelectrical resistivity in earthquake monitoring and prediction. Single-separation array observation system has been primarily employed in these experiments. The measured resistivity by this system stands for the general contribution from its detection depth to the surface. As a result, the contribution from each layer cannot be determined by this system. Consequently, some workers have explored new observation systems and conducted experiments in lab/field on multi-separation array observation and electrical resistivity tomography. In the present paper, experimental results from single-separation array observation system are briefly described, while those from multi-separation array observation and electrical resistivity tomography are introduced and generalized in detail, and at last possible new research interests are suggested.